Influence of nozzle temperature, bed temperature, and printing speed on the tensile strength of 3D-printed PLA specimens - Al-Shalawi, Faisal Dakhelallah; Mohamed Ariff, Azmah Hanim; Mohd Ariffin, Mohd Khairol Anuar; Seng Kim, Collin Looi; Brabazon, Dermot (Penerbit UTM Press, 2025)
Additive Manufacturing (AM), or 3D printing, revolutionises modern manufacturing by reducing material waste and enabling the creation of complex geometries through layer-by-layer construction from digital files. Its environmental efficiency and versatility, particularly with materials like biodegradable Polylactic Acid (PLA), align with global sustainability goals and cater to diverse industries, from healthcare to aerospace. As ongoing research enhances PLA's properties and sustainability, AM's adoption across various sectors is poised to expand, solidifying its role as a transformative technology. This investigation examined the impact of nozzle temperature on the tensile strength of PLA specimens produced by a 3D printer, considering different bed temperatures and printing speeds. The experiment involved varying the nozzle temperature (190°C, 200°C, 210°C), bed temperature (35°C, 45°C, 55°C, 65°C), and printing speed (50 mm/s, 60 mm/s, 70 mm/s, 80 mm/s), while maintaining all other variables constant. The specimens were printed using a raster angle of (90°, 0°, 0°) and a grid infill pattern. The tensile strength of the specimens was assessed using a tensile testing machine. The recorded tensile strength values of the PLA samples produced through 3D printing exhibited a decrease with increasing nozzle temperature, bed temperature, and printing speed. However, the measured tensile strength values remained approximately consistent. There was an elevation in tensile strength at a nozzle temperature of 200°C, bed temperature of 45°C, and printing speed of 60 mm/s. It may be deduced that the examined parameters do not exert a substantial influence on the tensile strength of the specimens. Consequently, it is advisable to undertake further investigation to scrutinise the implications of these parameters on other aspects of the material properties.